Fibroblast Growth Factor-23 (FGF-23) in Patients with Regular Hemodialysis: A Risk Factor for Restless Legs Syndrome - Harahap, Rasyidah Hasan; Riri Andri Muzasti; Alwi Thamrin Nasution (Journal of Endocrinology, Tropical Medicine, and Infectious Disease (JETROMI), 2020)
Background: Restless Legs Syndrome (RLS) is one of the most common sleep disturbance problems in dialysis patients. In this study, we would like to explore some of bone and mineral marker disorder especially fibroblast growth factor-23 (FGF-23)and its correlation with RLS in regular hemodialysis patients. Methods: This is a cross sectional study design involving 71 respondents with chronic kidney disease that already had regular hemodialysis at Haji Adam Malik Hospital Medan. Status of RLS in this patients were being evaluated according to the International Restless Leg Syndrome Study Group (IRLSG) by interviewing and laboratory examination of FGF-23, hemoglobin (Hb), serum iron (SI), total iron binding capacity (TIBC), transferrin saturation (TSAT), serum ferritin, calcium (Ca) and phosphate (P) level. Results: Of all study subjects, 26 respondents (34.6%) diagnosed with RLS. Bivariate analysis result showed that there is a relationship between FGF-23, hemoglobin, phosphate, and transferrin saturation level with RLS. Logistic regression analysis used to see the most dominant factor of all. Conclusion This study conclude that increase in FGF-23 levels can increase the risk of RLS. However, FGF-23 is not the most dominant risk factor for RLS in regular hemodialysis patients.